Gliders for passive acoustic monitoring of the oceanic environment - Cauchy, Pierre; Heywood, Karen J.; Merchant, Nathan D.; Risch, Denise; Queste, Bastien Y.; Testor, Pierre (Frontiers in Remote Sensing, 2023)
Ocean gliders are quiet, buoyancy-driven, long-endurance, profiling autonomous platforms. Gliders therefore possess unique advantages as platforms for Passive Acoustic Monitoring (PAM) of the marine environment. In this paper, we review available glider platforms and PAM systems, and explore current and potential uses of PAM-equipped gliders for the study of physical oceanography, biology, ecology and for regulatory purposes. We evaluate limiting factors for PAM glider surveys, such as platform-generated and flow noise, weight, size and energy constraints, profiling ability and slow movement. Based on data from 34 PAM glider missions, it was found that <13% of the time spent at sea was unsuitable for PAM measurements, either because of surface communications or glider manoeuvre, leaving the remainder available for subsequent analysis. To facilitate the broader use of PAM gliders, we document best practices and include workarounds for the typical challenges of a PAM glider mission. Three research priorities are also identified to improve future PAM glider observations: (i) technological developments to improve sensor integration and preserve glider endurance; (ii) improved sampling methods and statistical analysis techniques to perform population density estimation from PAM glider observations; and (iii) calibration of the PAM glider to record absolute noise levels, for anthropogenic noise monitoring. It is hoped this methodological review will assist glider users to broaden the observational capability of their instruments, and help researchers in related fields to deploy PAM gliders in their studies.